Primary and secondary central nervous system lymphoma - Kisiel, Elżbieta; Wosztyl, Anna (Contemporary Oncology/Współczesna Onkologia, 2004)
Primary central nervous system lymphoma (PCNSL). Primary central nervous system lymphoma (PCNSL) is an aggressive B-cell lymphoma that occurs in immunocompetent and immunosuppressed patients. Primary ocular lymphoma represents an important variant of this disease. The incidence of PCNSL is increasing in immunocompetent patients over the age of 60 for unexplained reasons. However, the incidence of AIDS-related PCNSL, which is related to Epstein-Barr virus infections, has fallen due to the institution of highly active antiretroviral therapy. High-dose methotrexate (MTX) is the single most active agent in the treatment of PCNSL. While standard- -dose MTX does not cross the blood-brain barrier, doses ł3.5 g/m 2 yield tumoricidal levels in the CSF. Therefore, most treatment regimens now incorporate high-dose MTX (1 to 8 g/m 2 ) alone or in combination with other chemotherapeutic agents. Craniospinal RT does not confer any additional survival benefit and is associated with significant neurotoxicity, limiting the administration of subsequent chemotherapy. Given the increased risk of treatment-related neurotoxicity, especially among elderly patients, several authorities recommend deferring radiotherapy until relapse in this population. Secondary central nervous system lymphoma (SCNSL). There is a close correlation between histological subtype of lymphoma and probability of the occurrence of SCNSL. The same correlation was also drawn between SCNSL and involvement of bone marrow, the testis or paranasal sinuses. Burkitt’s lymphoma and lymphoblastic lymphoma both have a high incidence of SCNSL, therefore patients now receive both intrathecal chemotherapy and high doses of MTX or cranial irradiation. Follicular lymphoma and the other lymphocytic lymphomas have been shown to have a probability of CNS infiltration below 1%, thus there can be no justification for prophylaxis. The incidence of secondary central nervous system occurrences in other types of HNHL is not sufficiently high to warrant the use of CNS prophylaxis in all patients, however, it is connected with very poor prognosis. Further analysis confirmed 5 factors to have an independent impact on CNS involvement: age, LDH, albumin, retroperitoneal nodes, and number of extranodal sites. Patients with HNHL should receive adequate CNS prophylaxis if at least four of the five risk factors identified are present. If it is difficult to select the appropriate group to receive CNS prophylaxis, it is equally difficult to determine what constitutes the best prophylaxis. Some of the data reported above suggest that intrathecal therapy and systemic MTX may reduce the risk of SCNSL.